Mesothelial Physiology and Pathophysiology - Sotirios G. Zarogiannis (Frontiers Research Topics, 2018)
The mesothelium is composed by a single layer of mesothelial cells that vest the serosal cavities (pleural, peritoneal and pericardial) and internal organs of the body. The mesothelial cells have a mixed phenotype of epithelial cells and fibroblasts rendering them remarkable plasticity. Besides providing a slippery surface for the frictionless movement of internal organs, the mesothelium participates in a wide range of physiological and pathophysiological processes. Some of its functions include lung development, trans-cellular and para-cellular transport of ions and water, secretion of glycoproteins (mainly hyaluronan), secretion of cytokines and growth factors, wound healing, response to inflammatory stimuli and induction of inflammation, mesothelial to mesenchymal transition and formation of tunneling nanotubes. Many of these functions are pivotal to physiological conditions such as respiratory development, maintenance of steady volume of serosal fluids and serosal permeability, cell-to-cell communication, re-mesotheliazation of serosal membranes after mechanical (e.g. by asbestos or nanoparticles) or inflammatory injury and participation in immune responses. Deviation from the physiological threshold of these functions results in the development of serosal effusions, induction of serosal and lung fibrosis, induction of mesothelial tumorigenesis, leading thus to devastating pathologies. Treatment of pathologies like mesothelioma, pleural and peritoneal fibrosis (in cases of patients under Peritoneal Dialysis) or lung fibrosis still pose a great challenge for researchers.